The development of proton-electron math e-comic to improve special needs students’ mathematical concepts understanding - Yulyanti Harisman; Fitrani Dwina; Minora Longgom Nasution; Mohd Hasril Amiruddin; Hamdani Syaputra (Jurnal Infinity, 2023)
Technology-based learning media is still lacking for special needs students in mathematics. Based on observations and interviews with Special School (SLB) teachers, the learning media used were still monotonous, such as picture books and writing using a blackboard. This research aims to develop e-comic math using the App Pixton application, which is valid and practical for children with special needs in SLB. The research method used is Plomp model development research in the prototype development phase: self-evaluation, expert review, and one-to-one evaluation. The data collection instruments used were a questionnaire and mathematical concepts on addition and subtraction topics for students with special needs. The research subjects were 21 students and 5 teachers from 5 different special schools in 5 West Sumatra, Indonesia cities. The study results show that the media developed is valid and practical for students with deaf and intellectual disabilities. This research implies that teachers must be able to develop other IT-based learning media to help students with special needs learn mathematics like normal children.